2013
DOI: 10.4103/0974-620x.122268
|View full text |Cite
|
Sign up to set email alerts
|

Angle Kappa and its importance in refractive surgery

Abstract: Angle kappa is the difference between the pupillary and visual axis. This measurement is of paramount consideration in refractive surgery, as proper centration is required for optimal results. Angle kappa may contribute to MFIOL decentration and its resultant photic phenomena. Adjusting placement of MFIOLs for angle kappa is not supported by the literature but is likely to help reduce glare and haloes. Centering LASIK in angle kappa patients over the corneal light reflex is safe, efficacious, and recommended. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
60
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(64 citation statements)
references
References 30 publications
1
60
0
2
Order By: Relevance
“…32 The µ-chord, which is correlated with kappa angle, 26,33 has been hypothesized to be related with the visual performance achieved with MIOLs. 34 However, to this date, there is only one clinical study that correlates the kappa angle with the visual performance. Prakash et al 3 confirm if this range of temporal decentration increases or not the risk of the symptoms as has been hypothesized.…”
Section: Discussionmentioning
confidence: 99%
“…32 The µ-chord, which is correlated with kappa angle, 26,33 has been hypothesized to be related with the visual performance achieved with MIOLs. 34 However, to this date, there is only one clinical study that correlates the kappa angle with the visual performance. Prakash et al 3 confirm if this range of temporal decentration increases or not the risk of the symptoms as has been hypothesized.…”
Section: Discussionmentioning
confidence: 99%
“…The larger the discrepancy between the visual axis and pupillary axis or visual axis and optical axis is, which decreased the visual quality. In the MIOLs of eyes with a large angle kappa, the light might pass the center of the macula through other diffractive rings instead of the central area of the MIOLs, which is also known as functional IOL decentration [10], thereby leading to the photic phenomena and surgical aberrations [11,12]. Therefore, according to the angle kappa, adjusting the position of the MIOLs may help reduce photic phenomena [11,13].…”
Section: Discussionmentioning
confidence: 99%
“…In the MIOLs of eyes with a large angle kappa, the light might pass the center of the macula through other diffractive rings instead of the central area of the MIOLs, which is also known as functional IOL decentration [10], thereby leading to the photic phenomena and surgical aberrations [11,12]. Therefore, according to the angle kappa, adjusting the position of the MIOLs may help reduce photic phenomena [11,13]. In addition, some studies also indicated that more than 0.5 mm of preoperative angle kappa should be carefully considered in cataract patients implanted with diffractive or refractive types of MIOLs [6,11,14].…”
Section: Discussionmentioning
confidence: 99%
“…The difference between the visual axis and the pupillary axis is quantified by the angle kappa and is on the order of 58. 34,35 The current MRI methods do not provide a high enough spatial resolution either to detect the foveal pit, needed to define the visual axis, or to measure the center of the pupil and the perpendicular intersection with the cornea, needed to reconstruct the pupillary axis. Therefore a different axis is defined, which can be geometrically reconstructed from the MR images.…”
Section: Discussionmentioning
confidence: 99%